Synthesis and antimicrobial evaluation of Histidine Cinnamaldehyde Schiff base containing structural feature of 1, 3, 4-thiadiazole heterocyclic moiety - Doaa Mahmood Ibrahim; Karima Fadhil Ali; Mayada Hadi Abd_alwahab (College of Pharmacy / Mustansiriyah University, 2020)
Reaction of aqueous solution of amino acid Histidine with ethanolic solution Cinnamaldehyde to synthesize the desired Schiff base. Then, the derivative of 1, 3, 4-thiadiazole ring have been synthesized by reaction of the imine derivative with Thiosemicarbazide in presence of POCL3. The entire intermediate and final compound characterized and identified by elemental microanalysis as melting point, FT-IR spectra, 1H-NMR spectroscopy. Agar Well Diffusion method evaluated the antimicrobial activity on gram positive bacteria such as Staphylococcus aureus and Streptococcus pneumonia and gram-negative bacteria such as E coli & Acinetobacter species and also antifungal activity had been studied on one type of fungi (candida albicans).